Knowledge, attitude and practice of diabetes among secondary school-going children in Bangladesh - Akter, Farhana; Rashid, S. M. Mahbubur; Alam, Nazmul; Lipi, Nasrin; Qayum, Md. Omar; Nurunnahar, Mehejabin; Mannan, Adnan (Frontiers in Public Health, 2022)
Diabetes Mellitus (DM) is a global public health concern. DM has been increasing alarmingly among the young people and childhood-onset has now become an emerging issue worldwide. Unlike other chronic diseases, DM requires constant and active attention of the patients, sometimes of their family members for successful management of this disease. Knowledge, attitude, and practices make significant differences at the population level, which largely depend on socioeconomic status, area of residence, level of education, and other socio-demographic attributes. A descriptive cross-sectional study was carried out among secondary school students in grades 6 through 10 attending schools in 18 districts of Bangladesh. A total of 2009 students were enrolled for the study from the selected schools and madrasas from Bengali, English, and Arabic medium. The majority of responders (79.34%) reported that they had heard of diabetes, however, only 45% knew that diabetes can cause blood glucose levels to rise. Among different therapeutic options, only 15% of students had heard the name of metformin, while 56.2% were familiar with insulin. English medium students were significantly more likely to have good knowledge than the Bangla medium students (19.31%, OR: 1. 44; 95% CI: 1.07, 1.95). Respondents of semi-urban (19.66%, OR: 1.7; 95% CI: 1.21, 2.36) and urban (18.47%, OR: 1.48; 95% CI: 1.17, 1.86) areas were more likely to have good knowledge than rural areas. Of the respondents, 20.61% did not know of any diabetic treatment options. Only a small percentage of students (11%) attended any diabetes education classes and 10.7% of students followed any recommended diabetes prevention methods. Knowledge, attitude, and practice related to diabetes were found to have been influenced by socioeconomic factors, societal practices, and behavioral patterns. This is the first nationwide research study in Bangladesh among secondary school students to study knowledge, attitudes, and practices related to diabetes. With a focus on Bangladesh's youthful population, this study sought to provide an informational framework that can be supportive for effective intervention to increase knowledge of diabetes and its implications.